2020
DOI: 10.1186/s12958-020-00659-z
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate protects against radiation-induced ovarian injury in female rats—impact on mitochondrial-related genes

Abstract: The toxic effects of ionizing radiation on the gonads have been widely recognized. Sphingosine 1-phosphate (S1P) has a protective effect on ovarian injury, and although it is known that mitochondria are involved in this process, the specific mechanism is not fully understood. The present study analysed the changes in the serum AMH and ovarian histology in Sprague-Dawley female rats exposed to X-ray radiation only or co-administered with S1P. The mRNA expression profile of ovarian tissue was further analysed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…S1P has been shown to inhibit granulosa cell apoptosis in ovaries and promote ovarian autoangiogenesis [ 19 ]. Furthermore, exogenous administration of S1P was shown to protect the ovarian follicle reserve by decreasing apoptosis during chemoradiotherapy [ 20 – 23 ], improve the survival rate of cryopreserved ovaries, increase the vascular density in ovarian grafts, and promote angiogenesis of the transplanted ovaries [ 24 , 25 ]. Nevertheless, S1P has a short half-life and cannot maintain long-term effects in vitro culture [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…S1P has been shown to inhibit granulosa cell apoptosis in ovaries and promote ovarian autoangiogenesis [ 19 ]. Furthermore, exogenous administration of S1P was shown to protect the ovarian follicle reserve by decreasing apoptosis during chemoradiotherapy [ 20 – 23 ], improve the survival rate of cryopreserved ovaries, increase the vascular density in ovarian grafts, and promote angiogenesis of the transplanted ovaries [ 24 , 25 ]. Nevertheless, S1P has a short half-life and cannot maintain long-term effects in vitro culture [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The third shared gene is UQCRH, which is responsible for the electron transfer between cytochrome C and cytochrome C1, representing a part of the most critical step in the electron transfer cascade and being involved in the oxidative phosphorylation of mitochondria. In addition, UQCRH can protect the ovaries of animals from radiation-caused damage 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Indigenous sheep use these genes to increase the reproductive rate and achieve multiple birth rates, directly or indirectly and in different ways, which is necessary for the continuation of the population in harsh environments. F13A1 improves heat stress tolerance of ewes 68 , while UQCRH protects the organisms from radiation-induced ovarian damage 67 , which is essential for sheep living in desert environments. As for CCDC178 and CNGA1, they are involved in immune repair 77 , 78 , while GLIS3 71 73 and GNAQ 76 are involved in stable fetal organ development.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have demonstrated that aberrations related to sphingolipids are the culprit of insulin resistance and mitochondrial dysfunction in T2DM. 149,150 Plasma S1P concentration is reportedly low in T2DM 151 and in diabetic complications, such as cardiovascular autonomic neuropathy, 152 obesity, 153 and vascular dysfunction. 153 Moreover, the mechanisms of S1P axis action and insulin signal transduction in hepatocytes, skeletal muscle cells, adipocytes, and pancreatic β-cells have been extensively discussed.…”
Section: The Involvement Of the S1p Axis In T2dmmentioning
confidence: 99%
“…Indeed, the development of T2DM is often associated with intracellular lipid dysregulation. Numerous investigators have demonstrated that aberrations related to sphingolipids are the culprit of insulin resistance and mitochondrial dysfunction in T2DM 149,150 . Plasma S1P concentration is reportedly low in T2DM 151 and in diabetic complications, such as cardiovascular autonomic neuropathy, 152 obesity, 153 and vascular dysfunction 153 .…”
Section: The Role Of the S1p Axis In Metabolic‐related Diseasesmentioning
confidence: 99%